An architecture for assisted navigation in intelligent environments. (2nd December 2009) - Abascal, J.; Lafuente, A.; Marco, A.; Falco, J.M.; Casas, R.; Sevillano, J.L.; Cascado, D.; Lujan, C.
The AmbienNet project aims to demonstrate the viability of navigation systems to assist users with or without disabilities supported by intelligent environments. In particular, people with sensorial, physical or cognitive disabilities can be highly benefited by these intelligent environments, whenever they satisfy their accessibility requirements. Thus, diverse heterogeneous technologies at different levels (network, hardware and middleware) have been developed by AmbienNet, making them interact with each other. Specifically, AmbienNet has developed a multi-cell indoor people localisation system, a network of sensors and intelligent wheelchairs (acting like autonomous mobile platforms). The resource management depends on a middleware layer that recognises high-level dynamic contexts (network scope independent) and provides continuity and high availability. On top of these elements, a new 'context and location services level' is being developed in order to process the data provided by the sensors and the localisation system. This level will allow the provision of abstract information to the services offered by the intelligent environments. As a demonstration, a navigation application to support intelligent wheelchairs for users with disabilities and a handheld guide application for users with mild cognitive disabilities are being developed.